A novel pivot ankle/foot prosthesis reduces sound side loading and risk for osteoarthritis: a pragmatic randomized controlled trial. Issue 3 (10th June 2022) - Runciman, Phoebe; Cockcroft, John; Derman, Wayne
Abstract : Background: Individuals with unilateral transtibial amputation are at risk of abnormal mechanical joint loading and development of osteoarthritis on sound side joint structures. Objectives: This study describes the spatiotemporal and kinetic and kinematic parameters related to osteoarthritis in participants while using (A) a solid-ankle cushioned-heel prosthesis (SACH), (B) a conventional energy storage and return (ESAR) foot prosthesis, and (C) a novel ESAR (N-ESAR) foot prosthesis. Study design: A pragmatic randomized controlled trial. Methods: K3–K4 ambulators used three feet in a 2-week randomized cross-over order. Kinetics of vertical ground reaction forces (vGRFs) and 3D kinematics of joint angles were integrated to provide normalized parameters. Data were analyzed using one way and mixed model Analysis of variance (ANOVAs) ( p < 0.05) and Cohen d statistic. Results: Twenty participants, aged 40 ± 16 years with body mass index of 24.7 ± 3.6 kg/m 2, experienced minimal change in the spatiotemporal parameters between feet. Participants using the N-ESAR foot prosthesis experienced reduced peak knee external adduction moment ( p = 0.030), peak vGRFs ( p < 0.001), and peak loading rate of vGRFs ( p = 0.030). Peak knee flexion moments only changed when using the solid-ankle cushioned-heel prosthesis, in a positive direction ( p = 0.014). Using the N-ESAR prosthesis also increased peak distal shank power during late stance phase ( p < 0.001). Conclusions: A novel ankle/foot ESAR prosthesis reduces loading on the sound side. With extended use of the N-ESAR foot prosthesis, these findings may provide the prosthesis user with improved outcomes related to sound side loading and development of osteoarthritis.